Estudo de técnicas para o tratamento alternativo de efluentes oleosos oriundos da industrialização da castanha de caju - Jerônimo, Carlos Enrique de Medeiros (2010)
An evaluation project was conducted on the technique of treatment for effluent oil which is the deriving process to improve cashews. During the evaluation the following techniques were developed: advanced processes of humid oxidation, oxidative processes, processes of biological treatment and processes of adsorption. The assays had been carried through in kinetic models, with an evaluation of the quality of the process by means of determining the chemical demand of oxygen (defined as a technique of control by means of comparative study between the available techniques). The results demonstrated that the natural biodegradation of the effluent ones is limited, as result using the present natural flora in the effluent one revealed impracticable for an application in the industrial systems, independent of the evaluation environment (with or without the oxygen presence). The job of specific microorganisms for the oily composite degradation developed the viability technique of this route, the acceptable levels of inclusion in effluent system of treatment of the improvement of the cashew being highly good with reasonable levels of removal of CDO. However, the use combined with other techniques of daily pay-treatment for these effluent ones revealed to still be more efficient for the context of the treatment of effluent and discarding in receiving bodies in acceptable standards for resolution CONAMA 357/2005. While the significant generation of solid residues the process of adsorption with agroindustrial residues (in special the chitosan) is a technical viable alternative, however, when applied only for the treatment of the effluent ones for discarding in bodies of water, the economic viability is harmed and minimized ambient profits. Though, it was proven that if used for ends of I reuse, the viability is equalized and justifies the investments. There was a study of the photochemistry process which have are applicable to the treatment of the effluent ones, having resulted more satisfactory than those gotten for the UV-Peroxide techniques. There was different result on the one waited for the use of catalyses used in the process of Photo. The catalyses contained the mixing oxide base of Cerium and Manganese, incorporated of Potassium promoters this had presented the best results in the decomposition of the involved pollutants. Having itself an agreed form the gotten photochemistry daily paytreatment resulted, then after disinfection with chlorine the characteristics next the portability to the water were guarantee. The job of the humid oxidation presented significant results in the removal of pollutants; however, its high cost alone is made possible for job in projects of reuses, areas of low scarcity and of raised costs with the capitation/acquisition of the water, in special, for use for industrial and potable use. The route with better economic conditions and techniques for the job in the treatment of the effluent ones of the improvement of the cashew possesses the sequence to follow: conventional process of separation water-oil, photochemistry process and finally, the complementary biological treatment